Energy Restriction Decreases Triglyceride Turnover in Subcutaneous and Visceral Adipose Tissue, but Has No Effect on Hepatic De Novo Lipogenesis in Obese Zucker Rats. (29th May 2020) - Dawson, M Alan; Hennigar, Stephen; McClung, James; Shankaran, Mahalakshmi; Nyangau, Edna; Evans, William; Hellerstein, Marc; Field, Tyler; Kelley, Alyssa; Anderson, Bradley; Pasiakos, Stefan; Berryman, Claire
Abstract: Objectives: Obesity is associated with increased hepatic de novo lipogenesis (DNL) and altered triglyceride (TG) turnover. A previous trial in male Sprague Dawley rats demonstrated that both energy restriction and higher protein diets downregulate hepatic DNL. It is unknown whether energy restriction and higher protein diets alter kinetic measures of lipid metabolism in obese rodents. The present study examined the effects of energy restriction and dietary protein content on tissue-specific lipid kinetics in obese Zucker rats. Methods: Six-week-old female obese Zucker rats (Lepr fa+/fa+ ; n = 48) were randomized into one of four groups: ad libitum (AL) standard AIN-93 M diet (14% protein, 9% fat, 3 mg cholesterol/100 g feed), 60% energy-restricted (ER) diet, ad libitum high protein (AL + PRO) modified AIN-93 M diet (35% protein, 9% fat, 7.2 mg cholesterol/100 g feed), or a 60% energy-restricted high protein (ER + PRO) diet. Using 2 H2 O labeling and mass isotopomer distribution analysis, DNL, TG turnover, and de novo cholesterol synthesis were measured in hepatic, subcutaneous adipose tissue (SAT), and visceral adipose tissue (VAT) after 10 weeks of feeding. Two-way ANOVA and post-hoc Tukey pair-wise comparisons were performed. Results: Energy restriction, independent of protein content, resulted in less body mass gain (main effect, P < 0.05), although there were no differences in body fat % (ER: 50.8 ± 2.8%, ER + PRO: 50.5 ± 3.7%, AL: 47.3 ± 5.3%, AL + PRO: 50.0 ± 5.3%; P > 0.05). Energy restriction decreased TG turnover in SAT and VAT (main effect, P < 0.05), increased the contribution from DNL versus other sources to newly deposited TG in VAT ( P < 0.01), did not change total DNL in VAT or liver ( P > 0.05) but reduced DNL in SAT ( P < 0.01), and increased hepatic, SAT, and VAT de novo cholesterol synthesis ( P < 0.01). Dietary protein had no effect on lipid kinetics. Conclusions: In obese Zucker rats, hepatic DNL was not altered by energy restriction or higher protein feeding. However, energy restriction did decrease TG turnover in SAT and VAT. In a leptin-deficient rodent model of obesity, energy restriction had differential effects on various measures of lipid metabolism. Funding Sources: DMRP/USAMRDC. Views expressed are those of the authors and do not reflect the official policy of the Army, DoD, or U.S. Government.